Association of C-Reactive Protein with Parameters of Early Onset Sepsis and Blood Culture - Azizullah Langah, Naseer Ahmed Memon, Sereena Awan, Yousra Shafiq, Benish Zafar, Muhammad Adil Ramzan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Blood culture is a gold standard technique to diagnose neonatal sepsis but the C-reactive protein (CRP) is also an important biomarker of acute phase reaction. CRP has a role in humoral immunity against infection, leading to inflammation. Very few of the data is available to conclude the diagnostic accuracy of CRP in association with parameters of early stage neonatal sepsis in pre-term or low birth weight babies. So the aim of current study was to find out the association of C-reactive protein with parameters of early onset sepsis and blood culture in pre-term and low birth weight babies. Methods: A cross-sectional study was conducted at the Pediatric Medicine department of Maternal and Child Health Center (MCH), Shaheed Benazirabad during August 2022 to January 2023. Early onset sepsis was diagnosed on the basis of maternal factors, prenatal history and clinical examination. Blood sample was collected and sent to the pathology laboratory of Peoples University of Medical and Health Sciences for Nawabshah for measurement of C-reactive protein, white blood cell count and culture and sensitivity testing. Data was analyzed by using the Statistical Package for Social Science (SPSS) version-20. p-value less than 0.05 was considered as significant. Results: A total of 120 patients of neonatal sepsis were enrolled in the study out of them 52 were positive for C-reactive protein. The mean age of the study participants was 1.6 ±0.69 days. Male participants were predominant (63.5%) over their female counterpart. Majority cases of septicemia (57.7%) were having birth weight less than 2.5kg. Odd ratio of C-reactive protein was estimated at 95% confidence interval and the results found that age had significant association with positive C-reactive protein. Birth weight less than 2.5kg also showed significant negative association with C-reactive protein but the term of birth found no any significant association. Patients having positive blood culture and those who had WBC count more than 25000/mm3 reported strongly significant association with C-reactive protein. Conclusion: It can be concluded that the C-reactive protein is significantly associated with parameters like age, WBC count more than 25000/mm3 and blood culture but no association has been found with maturity of neonate i.e. term or pre-term babies. The birth weight less than 2.5kg is negatively associated with the C-reactive protein. Keywords: Neonatal sepsis, C-reactive protein, Pre-term